Overview of Midwives’ Knowledge of Postpartum Bleeding to Reduce Maternal Mortality Rate In Working Area at Pelabuhan Ratu Hospital - Apriliyani, Sinta Nur; Tjahja, Raden (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Introduction:The Maternal Mortality Rate indicator shows the level of risk of maternal death during pregnancy, childbirth, and the postpartum period per 100,000 live births in a given area over a certain period. According to the district health profile report, Maternal deaths in 2023 reached 792 cases or 96.89 per 100,000 live births, an increase of 114 cases compared to 2022 which recorded 678 cases. In 2022 Sukabumi district common causes of maternal death are hemorrhage 14 case and 7 case in 2023Methods:Study used a descriptive approach with a cross-sectional design involving 74 midwives. The sampling technique was random sampling. Data were obtained through the use of questionnaires that focused on the variable of knowledge about postpartum hemorrhage. Data analysis was performed using the univariate analysis method.Results:It was found of 74 midwives in the working arae of Pelabuhan Ratu Hospital, the majority were 31-35 years old (43.2%), had D3 Midwifery educational background (59.5%), and had 11-15 years of work experience (33.8%). In addition, 77% not attended PPGDON training. Most midwives (55.4%) had a good understanding of postpartum hemorrhage. Conclusion:The majority of midwives in working area at Pelabuhan Ratu Hospital have good knowledge about postpartum hemorrhage.Gambaran Pengetahuan Bidan tentang Perdarahan Pascapersalinan untuk Menurunkan Angka Kematian Ibu di Wilayah Kerja RSUD Pelabuhan RatuAbstrakPendahuluan: Indikator Angka Kematian Ibu menunjukkan tingkat risiko kematian ibu pada masa kehamilan, persalinan, dan masa nifas per 100.000 kelahiran hidup di suatu wilayah selama periode tertentu. Berdasarkan laporan profil kesehatan daerah, kematian ibu pada tahun 2023 mencapai 792 kasus atau 96,89 per 100.000 kelahiran hidup, Hal ini meningkat 114 kasus dibandingkan tahun 2022 yang tercatat 678 kasus. Di Kabupaten Sukabumi tahun 2022 penyebab kematian ibu terbanyak adalah perdarahan 14 kasus dan tahun 2023 menjadi 7 kasus.Metode: Penelitian menggunakan pendekatan deskriptif dengan desain cross-sectional yang melibatkan 74 bidan. Teknik pengambilan sampelnya adalah random sampling. Data diperoleh melalui penggunaan kuesioner yang berfokus pada variabel pengetahuan tentang perdarahan postpartum. Analisis data dilakukan dengan menggunakan metode analisis univariat.Hasil: Ditemukan dari 74 bidan di wilayah kerja RS Pelabuhan Ratu, mayoritas berusia 31 – 35 (43,2%), berlatar belakang pendidikan D-3 Kebidanan (59,5%), dan memiliki pengalaman kerja 11 – 15 (33,8%). Selain itu, 77% tidak mengikuti pelatihan PPGDON. Sebagian besar bidan (55,4%) memiliki pemahaman yang baik mengenai perdarahan pascapersalinan. Kesimpulan: Mayoritas bidan di wilayah kerja RS Pelabuhan Ratu memiliki pengetahuan yang baik tentang perdarahan postpartum.Kata kunci: Bidan, Perdarahan Pascapersalinan, Pelabuhan Ratu